The evaluation of the calculation expenses during the standard jpeg compression method and the Krestenson-Levi method - Vasiura, A. S.; Kyrychenko, O. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The paper suggests to evaluate and to compare the calculation losses during the image compression by jpeg method and Krestenson-Levi compression method for image processing aimed at determining the most efficient conversion, which allows to reduce time for information transfer and improves the efficiency of the channel’s usage.